Pendidikan Kesehatan Dan Pelaksanaan Mengelola Risiko Dengan Cara Mengidentifikasi Keselamatan Pasien (Manajemen Risiko) Pada Mahasiswa Prodi Keperawatan Gigi - Pannyiwi, Rahmat; Idris, Idris; Betan, Abu Bakar; Samila, Samila; Nurhaedah, Nurhaedah; Sambo, Sri Wahyuni; Situmorang, Rupina Kanasia; Werdyaningsih, Endang (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Dental nursing students as prospective health workers must have the knowledge and ability to carry out patient safety measures. Students have received lecture material that is used as a basis for carrying out dental nursing actions or practicing in the room about patient safety. The purpose of Community Service is to manage risks by identifying patient safety (risk management). The method of implementing Community Service activities is health education and implementing risk management by identifying patient safety (risk management) followed by a questionnaire on the theme of patient safety pre-test and post-test. The results of implementing Community Service activities related to Dental Nursing Students' Knowledge in implementing patient safety targets are mostly good and sufficient.